Bioinspired manufacturing of oriented polysaccharides scaffolds for strong, optical haze and anti-UV/bacterial membranes. (15th October 2021) - Ling, Zhe; Liu, Wanying; Ren, Yuxuan; Chen, Hui; Huang, Caoxing; Lai, Chenhuan; Yong, Qiang
Abstract: Here, biomimetic dual esterification strategy was proposed on natural polysaccharides cellulose nanocrystals (CNCs) and galactomannan (GM) in combination with tartaric acid (TA) and benzoic anhydride (BA) respectively. Evaporation-induced self-assembly (EISA) formed the oriented quasinematic structure of the nanocomposites membranes. The CNCs crystallites were modified by TA and intercalated by amorphous polysaccharides, building a complex supramolecular network. Thus, it presents excellent light scattering property with the optical haze of ~90%, which was rarely reported previously. TA and BA simultaneously contributed to satisfying UV adsorption capability for the membranes, showing almost whole-spectra UVA/UVB blocking. Super high mechanical strength (>150 MPa) and toughness (~8 kJ/m 3 ) were revealed by the membranes with high addition amount of BA, together with the efficient antibacterial capability on both Gram-positive and negative bacteria. The diverse optical, mechanical and biological functions displayed by the polysaccharides membranes, propose new horizons on application for packaging, optoelectronic and biomonitoring sensors. Highlights: CNCs and GM nanocomposites membranes were fabricated via dual esterification. Super high optical haze was firstly achieved for CNCs based membranes. Chiral nematic structure of CNCs remained in the membranes showing birefringence. Optimal anti-UV/bacterial properties as well as mechanical strength were obtained.